Heavy metal pollution among autoworkers. II. Cadmium, chromium, copper, manganese, and nickel. - Clausen, J (1977)
Garages and auto-repair workshops may be polluted with other heavy metals besides lead. Blood of autoworkers with high lead content was analysed for cadmium, chromium, copper manganese, nickel, ALAD activity and carboxyhaemoglobin level. Cadmium and copper levels in blood of autoworkers were comparable with those of the control subjects while chroimium and nickel levels were significantly higher (P less than 0-01 for both metals), and scattered raised values of manganese were found. There was no significant mutual correlation between levels of various heavy metals determined in whole blood. High copper levels were slightly related to decreasing ALAD activity (P less than 0-1). Nineteen per cent of autoworkers were found to have an abnormally blood level of carboxyhaemoglobin. The amount of particulate heavy metal in autoworkshop air was not related to biochemical abnormalities found in the autoworkers. Various sources of pollution of these heavy metals in autoworkshops are discussed.